2006
DOI: 10.2755/jcmm010.004.08
|View full text |Cite
|
Sign up to set email alerts
|

The IL - 6 promoter polymorphism is associated with disease activity and disability in systemic sclerosis

Abstract: Systemic sclerosis (SSc) is a rare, autoimmune disease characterized by cutaneous and visceral fibrosis. Interleukin-6 (IL-6) is involved in the pathogenesis of many immune-mediated diseases. IL-6 plays an important role in the initiation and promotion of fibrosis. The polymorphism in the position -174 (G/C) of the promoter region of the IL-6 gene (IL-6 pr) may alter the expression of the gene. Complete linkage disequilibrium was observed between the -174 and -597 alleles. The aim of this study is to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It is involved in the pathogenesis of many immune-mediated diseases including SSc (8991). IL-6 is a classic inflammatory cytokine produced by various cells and involved in B cell differentiation, induction of acute phase proteins in liver cells, proliferation, and differentiation of T cells (92, 93).…”
Section: Interferon Inducible Cytokines and Chemokines In Sclerodermamentioning
confidence: 99%
“…It is involved in the pathogenesis of many immune-mediated diseases including SSc (8991). IL-6 is a classic inflammatory cytokine produced by various cells and involved in B cell differentiation, induction of acute phase proteins in liver cells, proliferation, and differentiation of T cells (92, 93).…”
Section: Interferon Inducible Cytokines and Chemokines In Sclerodermamentioning
confidence: 99%
“…IL6-174 CC genotype occurred more than twice as often for patients (29.4%) as for healthy controls (12.4%) (P < 0.00001, OR = 2.86, 95% CI 1.7 -4.9). Another study by Sfrentcornateanu et al [12], carried out on IL-6 promoter polymorphism in systemic sclerosis patients, showed that the GG homozygosis was found to be associated with a higher degree of illness activity and disability in systemic sclerosis patients. In a study of systemic lupus erythematosus (SLE) patients carried out on rs1800795 polymorphism by Chua et al [11], significant association was observed at homozygous G genotype in SLE patients.…”
Section: Discussionmentioning
confidence: 95%
“…This genetic polymorphism of IL-6 was correlated only with the presence of gastrointestinal manifestations, not with skin and lung damage [ 50 ]. Other data obtained after studying 20 cases with SS support the link between IL-6 polymorphism, especially the homozygous GG form, and an active and disabling disease [ 51 ].…”
Section: Il-6 In Systemic Sclerosismentioning
confidence: 91%